Histopathology of Surgically Resected Fallopian Tubes with Special Emphasis on Serous Tubal Intraepithelial Carcinoma - Rajyalakshmi, Rallapalli; Srujana, Raparthi; Vijaya Bhaskar, Rani (Annals of Pathology and Laboratory Medicine, 2019)
Background: The fallopian tube, though very common surgical specimen is rarely studied. It is affected by a spectrum of lesions ranging from inflammatory to rare neoplasms. Recent studies suggest a precursor lesion for high grade serous carcinoma of the ovary in the fallopian tube mucosa and is known as serous tubal intraepithelial carcinoma. In the present study, we analyzed the histopathology of fallopian tube lesions including serous tubal intraepithelial carcinoma. Methods: All the fallopian tube specimens received were grossed according to protocol and were routinely processed and stained. Atypical proliferative lesions of mucosa were subjected to immunohistochemical markers p53 and ki67. Result: Out of 350, 106 specimens showed a spectrum of lesions, of which hydrosalpinx was the commonest. Rest of the lesions were chronic and acute salpingitis, tuberculous salpingitis and tubal endometriosis. We encountered a single case of primary serous carcinoma of the fallopian tube. Immunohistochemistry on ten cases of atypical mucosal proliferations confirmed a single case each of serous tubal intraepithelial carcinoma and serous tubal intraepithelial lesion. Conclusion: Though fallopian tube is unremarkable in most cases, thorough sampling can detect significant pathological lesions including precursor lesions.